ПЕРВАЯ НАХОДКА ЛЕТАЮЩЕГО ЯЩЕРА (PTEROSAURIA) В АРМЕНИИ - Аверьянов А.О.; Атабекян А.А. (My University, 2005)
A distal fragment of a radius of the pterosaur Azhdarchidae indet. from the Upper Turonian (Upper Cretaceous) of southern Armenia is described. It was found together with remains of ammonites and other marine invertebrates. This is the first record of a flying reptile in Transcaucasia.
Keywords: Мезозой::Меловая::Верхний::Туронский